SOLUBLE PROGRAMMED DEATH-1 (SPD-1) AND PROGRAMMED DEATH LIGAND 1 (SPD-L1) AS POTENTIAL BIOMARKERS FOR THE DIAGNOSIS AND PROGNOSIS OF GLIOMA PATIENTS - Liu, Shujun; Zhu, Yadi; Zhang, Chenxi; Liu, Jiajia; Lv, Hong; Zhang, Guojun; Kang, Xixiong (Journal of Medical Biochemistry, 2020)
Background: This study aimed at investigating the feasibility of testing for soluble programmed death-1 (sPD-1) and soluble programmed death ligand 1 (sPD-L1) in serum samples of glioma patients and to evaluate the diagnostic and prognostic value of these two soluble molecules.Methods: Serum samples collected from 70 glioma patients before surgery were designated as the pre-operative (Pre) group, samples obtained from 90 post-surgery glioblastoma patients were designated as the Post group, and samples from 20 healthy volunteers were used as controls. Peripheral blood sPD-1 and sPD-L1 levels were detected by using ELISA kits and compared among the groups. The associations of these soluble molecule levels with clinicopathological variables and tumour progression were investigated.Results: Among the three groups, the Pre group had the highest sPD-1 levels, whereas the median sPD-L1 level was significantly lower in the Post group than in the other two groups. The area under the curve (AUC) of sPD-1 (0.762) for diagnosis was similar to that of sPD-L1 (0.718). Higher serum levels of sPD-1 and sPD-L1 were present in samples of patients with more advanced brain tumours. KaplanMeier analysis showed that higher serum levels of sPD-1 (>11.14 pg/mL) and sPD-L1 (>63.03 pg/mL) might predict shorter progression-free survival times of glioma patients.Conclusions: This study showed that sPD-1 and sPD-L1 might be promising predictive biomarkers for the diagnosis and prognosis of glioma patients.